2013
DOI: 10.1364/oe.21.014907
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating polarization of light with ultrathin epsilon-near-zero metamaterials

Abstract: One of the basic functionalities of photonic devices is the ability to manipulate the polarization state of light. Polarization components are usually implemented using the retardation effect in natural birefringent crystals and, thus, have a bulky design. Here, we have demonstrated the polarization manipulation of light by employing a thin subwavelength slab of metamaterial with an extremely anisotropic effective permittivity tensor. Polarization properties of light incident on the metamaterial in the regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 41 publications
0
82
0
Order By: Relevance
“…This unique material dispersion leads to novel optical properties, such as negative refractive index in a waveguiding geometry, 1 nominally unbounded density of photonic states, 2 and the existence of an ENZ (epsilon-near-zero) wavelength range for one of the permittivity components. 3 Metamaterial development relies on nanofabrication of features much smaller than the wavelength, traditionally requiring expensive techniques, such as electron beam lithography, with difficulty in scaling up samples to practical sizes. Notably, there have been recent demonstrations of large-area fabrication of two types of hyperbolic metamaterials: anodized alumina membranes, filled with metal nanocolumns 4,5 and metallo-dielectric laminates.…”
Section: Introductionmentioning
confidence: 99%
“…This unique material dispersion leads to novel optical properties, such as negative refractive index in a waveguiding geometry, 1 nominally unbounded density of photonic states, 2 and the existence of an ENZ (epsilon-near-zero) wavelength range for one of the permittivity components. 3 Metamaterial development relies on nanofabrication of features much smaller than the wavelength, traditionally requiring expensive techniques, such as electron beam lithography, with difficulty in scaling up samples to practical sizes. Notably, there have been recent demonstrations of large-area fabrication of two types of hyperbolic metamaterials: anodized alumina membranes, filled with metal nanocolumns 4,5 and metallo-dielectric laminates.…”
Section: Introductionmentioning
confidence: 99%
“…We have used the inherent property of hyperbolic metamaterials to support broadband, in both frequency and wave vector, electromagnetic modes 34 with high LDOS to demonstrate on-demand routing of electromagnetic signals on a deep subwavelength scale. In particular, we have shown that the new effect of near-field interference enables the broadband mapping of light in space, depending on its polarization handedness.…”
Section: Discussionmentioning
confidence: 99%
“…A magnetic field x h perpendicular to the direction of light propagation is created by the Helmholtz coils. Alternating current with a circular frequency 2 from the generator is fed to the solenoid through a resistor 1 R . The resistor 1 R together with the solenoid self-inductance 1 L forms a phase-shifting circuit.…”
Section: Methodsmentioning
confidence: 99%
“…Control of the light polarization and measuring birefringence of materials has a significant value for fundamental and applied researches [1][2][3]. There are known methods for measuring of birefringence using a rotating phase plate   4  and an analyzer [4].…”
mentioning
confidence: 99%